Poor Eating Habits and Selected Determinants of Food Choice Were Associated With Ultraprocessed Food Consumption in Brazilian Women During the COVID-19 Pandemic - Smaira, Fabiana Infante; Mazzolani, Bruna Caruso; Esteves, Gabriel Perri; André, Heloisa C. Santo; Amarante, Milla Cordeiro; Castanho, Daniela Fernandes; Campos, Karen Jennifer de; Benatti, Fabiana Braga; Pinto, Ana Jéssica; Roschel, Hamilton; Gualano, Bruno; Nicoletti, Carolina Ferreira (Frontiers in Nutrition, 2021)
Background: The aim of this study was to investigate possible associations between food consumption and eating habits and food choice determinants in women during COVID-19 pandemic. Methods: This is a cross-sectional survey conducted in Brazil between June and September, 2020, during which time social distancing measures were in place. Results: Participants (n = 629) were aged 34.0 years and mostly within normal weight according to BMI (60.4%). “Snacking” and “liking” associated with increased energy (β = 164.27 and β = 110.24) and carbohydrate intake (β = 1.97 and β = 1.80), and with reduced protein intake (β = −1.54 and β = −1.18). In contrast, “dieting” and “weight control” associated with reduced energy (β = −162.57 and β = −111.49) and carbohydrate intake (β = −2.78 and β = −2.07), and with increased protein intake (β = 3.78 and β = 1.65). “Dieting” (β = 7.27), “need and hunger” (β = 3.34), and “health” (β = 4.94) associated with an increased consumption of unprocessed and minimally processed foods, whereas “replacing main meals with snacks” (β = −8.98), “snacking” (β = −6.92) and binge eating symptoms (β = −0.34) associated with reduced consumption of foods within this processing level. In contrast, “use of delivery services” (β = 3.39), “replacing main meals with snacks” (β = 5.49), “visual appeal” (β = 2.17), “social norms” (β = 2.19) and “affect regulation” (β = 2.01) associated with increased ultraprocessed food consumption. Overall, associations were more frequent and pronounced when analyzing food consumption by processing level rather than by macronutrient intake. Conclusion: Some eating habits and food choice determinants (“snacking,” “replacing meals with snacks,” “use of delivery services”) observed during the COVID-19 pandemic were associated with an unhealthy diet (high energy and carbohydrate consumption, increased ultraprocessed food consumption and reduced unprocessed/minimally processed foods consumption) in Brazilian women.